The Application of GENRE KIT Snakes and Ladders to Enhance Adolescent Reproductive Health Knowledge: Quasi-Experimental Design - Darmayani, Ckristy Diana; Kumboyono, Kumboyono; Nugroho, Fajar Ari (Journal of Applied Nursing and Health, 2025)
Background: Adolescents constitute a significant portion of the global population and fall within the age range of 10–19 years. During adolescence, individuals undergo various physical, social, emotional, and hormonal changes. A lack of knowledge regarding reproductive health among adolescents is partly attributed to limited access to accurate and comprehensive information. This study aims to evaluate the effectiveness of the GenRe KIT Snakes and Ladders as an interactive educational tool to improve adolescents' knowledge about reproductive health. Methods: The research design used was a quasi-experimental design, with two groups, pre-test and posttest. The population consisted of adolescents, with a sample of 72 participants selected through simple random sampling. The inclusion criteria were adolescents 14-19 years old. A pretest was conducted before the intervention, followed by a posttest after the intervention. The instrument used was a modified Tentang Kita module by BKKBN, consisting of 21 knowledge and 13 attitude items related to reproductive health. Validity was confirmed with Pearson correlation values (r = 0.364–0.807), and reliability was high, with Cronbach’s alpha of 0.889 for knowledge and 0.745 for attitude. Results: The pre-test score in the intervention group was 13.11 (SD = 1.75) and improved significantly to 19.86 (SD = 1.33) after the intervention (p< 0.001). Post-intervention, the intervention group’s knowledge score remained substantially higher than the control group’s (p < 0.001). The between-group effect size (Cohen’s d = 3.48) indicated a very large effect, confirming the GenRe KIT Snakes and Ladders game's superior effectiveness in enhancing adolescents’ reproductive health knowledge compared to traditional lecture-based methods. Conclusion: GenRe KIT Snakes and Ladders game is effective in increasing adolescents' reproductive health knowledge and shows potential as an engaging educational tool in schools and community-based programs. Despite limitations related to study design, sample scope, and short intervention duration, the findings support further research using larger, more diverse populations and randomized designs to assess long-term impacts and behavioral outcomes.